THE ROLES OF TELESCREEN AND THOUGHT POLICE AS THE SURVEILLANCE MEDIA TO SUSTAIN TOTALITARIAN POWER IN GEORGE ORWELL’S NINETEEN EIGHTY-FOUR - SULAEMAN, TRIAN (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: literature, totalitarian, surveillance, Nineteen Eighty-Four.Surveillance becomes a major feature in panopticon prison which is promoted by Jeremy Bentham in eighteenth century. The word surveillance is derived from French language, surveiller, which means observing. Inside the prison, each individual is constantly monitored as a way of disciplined approach them to follow the rules. The thesis discusses about the surveillance is used by totalitarian governments to maintain power. George Orwell’s Nineteen Eighty-Fourdepicts the government and state oppression over its population. In which, every individual in the society is observed constantly as the effort to maintain the status quo.The writer specifically analyzes how the government maintaining its power by means of telescreen and Thought Police in Nineteen Eighty-Four. The writer combines Foucault’s panopticism and Hannah Arendt’s totalitarianism theories to approach the work  because those theories can help the writer to explore of how the totalitarian government maintain the status quo using the surveillance medium.The result of this research shows several functions from telescreen and Thought Police in surveillance medium as a means to maintain the totalitarian power. Telescreen functions as a surveillance practice can be divided into two major levels, societal and individual levels. While the Thought Police functions as a secret agent organization, which responsibles to operate surveillance system. Both are the government’s instruments which have important roles in maintaining the status quo of totaliarian regime.The writer’s suggestion for the further research’s Nineteen Eighty-Four, novel can be analyzed by using psychological approach because it depicts the psychological condition of individual and society whenever oppressed by the surveillance activities done by the government.